IMPLEMENTASI PROJEK PENGUATAN PROFIL PELAJAR PANCASILA (P5) TERHADAP DIMENSI KEBINEKAAN GLOBAL DI SD NAMIRA MELALUI PERMAINAN TRADISIONAL - Hattarina, shofia (AL-MUADDIB: Jurnal Kajian Ilmu Kependidikan, 2025)
This study focuses on the implementation of the Strengthening Pancasila Student Profile Project (P5) by emphasizing the global diversity dimension through traditional games at SD Namira. The primary objective is to enhance students' awareness of local culture, foster tolerance, and promote teamwork through tradition-based activities. A qualitative approach with a descriptive method was employed, utilizing data collected through observation, interviews, and documentation. The findings revealed that implementing P5 through traditional games such as congklak, gobak sodor, and jump rope effectively shaped students' character aligned with Pancasila values. These activities facilitated appreciation for cultural diversity, self-awareness, and improved social interactions in a globalized era.